O trabalho realizado por ONGs em Iguatu-CE na perspectiva da ética do cuidado - Carvalho, Eugenio Albuquerque de (2012)
This academic work aims to present the performance of the work done by the Association of Parents and Friends of Exceptional Children and The Marist Brothers Institute in the city of Iguatu-CE, under the gaze of the Ethics of Care. The text begins with a reference to the social situation of the municipality of Iguatu-CE, its origins and main activities developed by local and state managers. Next, a study is carried out on these institutions, focusing on its origins and taking into account the Down Syndrome (APAE) and the bibliography of Marcelino Champagnat (The Marist Brothers Institute). It is also an analysis of activities performed by organizations under the perspective of an Ethics of Care, based on the love of one s neighbor, solidarity and respect for differences, whether of a social, cultural or economic order, striving to put an end to discrimination and prejudice. Finally an assessment of activities and projects developed by the organizations mentioned above is promoted based on the physical and human resources and based on an Ethics of Care.